"One feels anger to know there is no one to help us!". Perceptions of mothers of children with Zika virus-associated microcephaly in Caribbean Colombia: A qualitative study - Elena Marbán-Castro; Cristina Enguita-Fernàndez; Kelly Carolina Romero-Acosta; Germán J. Arrieta; Anna Marín-Cos; Salim Mattar; Clara Menéndez; Maria Maixenchs; Azucena Bardají (Public Library of Science (PLoS), 2022)
Background The epidemic of Zika virus (ZIKV) was associated with a sudden and unprecedented increase in infants born with microcephaly. Colombia was the second most affected country by the epidemic in the Americas. Primary caregivers of children with ZIKV-associated microcephaly, their mothers mainly, were at higher risk of suffering anxiety and depression. Often, these women were stigmatized and abandoned by their partners, relatives, and communities. Methodology/Principal findings This study aimed to understand the perceptions about ZIKV infection among mothers of children born with microcephaly during the ZIKV epidemic in Caribbean Colombia, and the barriers and facilitators affecting child health follow-up. An exploratory qualitative study, based on Phenomenology and Grounded Theory, was conducted in Caribbean Colombia. Data were collected through In-Depth Interviews (IDI) from women who delivered a baby with microcephaly during the ZIKV epidemic at Clínica Salud Social, Sincelejo, Sucre District (N = 11). The themes that emerged during the interviews included experiences from their lives before pregnancy; knowledge about ZIKV; experiences and perceptions when diagnosed; considering a possible termination of pregnancy, and children's clinical follow-up. In some cases, women reported having been told they were having a baby with microcephaly but decided not to terminate the pregnancy; while in other cases, women found out about their newborn's microcephaly condition only at birth. The main barriers encountered by participants during children's follow-up included the lack of psychosocial and economic support, the stigmatization and abandonment by some partners and relatives, and the frustration of seeing the impaired development of their children. Conclusions This study contributed to identifying the social, medical, psychological, and economic needs of families with children affected by the ZIKV epidemic. Commitment and action by local and national governments, and international bodies, is required to ensure sustained and quality health services by affected children and their families. Author summary As of January 2018, nearly 4000 cases of children with congenital birth defects associated with Zika virus infection, included microcephaly, had been reported in the Americas. In 2019, we interviewed eleven mothers of children with microcephaly in Colombia, a country heavily affected by the Zika epidemic. Most women were young, lived in peri-urban areas were of low socioeconomic status, according to official government classification in Colombia. They reported knowing that the virus was transmitted by mosquitoes, and how to prevent mosquito bites, yet they were not aware of Zika infection being transmitted by sexual contact. Most women had been tested for Zika during pregnancy but did not receive their laboratory results. Also, they complained that they had not received enough information from healthcare providers. When fetal anomalies were detected prenatally, only a few of them were offered the possibility to terminate the pregnancy. Women reported a lack of both economic and psychosocial support to deal with the special health care needs their children required. The results of this study highlight the struggles and challenges of families of children severely affected by the Zika virus and provide valuable information for health policy making as part of the next epidemic preparedness and response.